2016
DOI: 10.1177/1087054716652617
|View full text |Cite
|
Sign up to set email alerts
|

Potential Social and Neurocognitive Benefits of Aerobic Exercise as Adjunct Treatment for Patients With ADHD

Abstract: Aerobic exercise may be a useful non-medication adjunct therapy for ADHD. The clinical effectiveness of aerobic exercise for ADHD in children and adults warrants further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Consequently, this necessitates that children with ADHD constantly engage their cognitive resources during the RSE to ensure the coordination of upper and lower limbs with the rope. Analyzing the mechanism of impact, RSE can improve WM by promoting neurotransmitters, such as catecholamines ( 23 ), which are similar to the mechanism of action of stimulant medications used to treat ADHD ( 42 ). It also enhances the secretion of dopamine, brain-derived neurotrophic factor (BDNF), and increases cerebral blood flow ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this necessitates that children with ADHD constantly engage their cognitive resources during the RSE to ensure the coordination of upper and lower limbs with the rope. Analyzing the mechanism of impact, RSE can improve WM by promoting neurotransmitters, such as catecholamines ( 23 ), which are similar to the mechanism of action of stimulant medications used to treat ADHD ( 42 ). It also enhances the secretion of dopamine, brain-derived neurotrophic factor (BDNF), and increases cerebral blood flow ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The medication treatment should be completed by non-pharmacological therapy. Authors also point out the necessity of conducting controlled clinical trials in adults and children (32).…”
Section: Physical Activity and Adhd Symptoms In Adultsmentioning
confidence: 99%
“…Aerobic exercises, structured physical exercise and various other forms of physical activities have been identified as effective strategies for alleviating ADHD symptoms and enhancing neuropsychological parameters (Kamp et al, 2014;Sun et al, 2022Sun et al, , 2024Zhu et al, 2023). Furthermore, engaging in physical exercise has been shown to augment the response to pharmacotherapy (Klil-Drori & Hechtman, 2016). Conversely, regular physical activity supports cognitive function improvement by facilitating brain plasticity, enhancing oxygenation and blood circulation, elevating neurotransmitter levels (such as serotonin and norepinephrine) and bolstering brain-derived neurotrophic factor (BDNF) levels within the neurological system (Kramer et al, 2004;Liu et al, 2015;Leckie et al, 2014).…”
mentioning
confidence: 99%
“…Smith et al (2013) reported that aerobic exercise training is associated with improved attention and processing speed, executive functions and memory in children with ADHD. Moreover, exercise was shown as beneficial for social behaviour, anxiety, and motor skills in these children (Klil-Drori & Hechtman, 2016). However, these studies investigated non-specific exercise programmes for children with ADHD.…”
mentioning
confidence: 99%
See 1 more Smart Citation